Pengembangan modul pembelajaran sistem bahan bakar mobil suzuki ertiga - Ari Gunawan; Rabiman Rabiman; Samsul Hadi (JURNAL VOKASI DEWANTARA (JVD), 2022)
AThis study aims to: (1) produce a learning module for the fuel (2) to determine the feasibility of the resulting fuel system module to be used as teaching material. This study is a research and development study with the development of learning media in the form of an injection fuel system module in Light Vehicle Engine Maintenance lessons for class XII students of the Automotive Light Vehicle Engineering expertise program. This research was carried out at SMK Negeri 2 Yogyakarta using the modified Four-D method by Thiagarajan and Semmel. This study involved material experts, media experts, subject teachers and students to get an assessment and response to the feasibility of the module. The data analysis technique used is descriptive analysis. The results showed that the development process of the Fuel Injection Gasoline System module was based on the defining stage, the design stage or initial information collection, the development stage, and the dissemination stage. The results of the module feasibility level assessment carried out by material experts obtained a 76.25% feasibility level with the very feasible category. According to media experts, the feasibility of the module is 68.75% in the very feasible category. The assessment of the feasibility level by subject teachers is 75% in the very feasible category. The response from students at SMK Negeri 2 Yogyakarta was 86.7% with a very decent category. The research shows that the module of the Fuel Injection Petrol System is suitable for use and the learning process at SMK Negeri 2 Yogyakarta. Keywords: Learning Module, Light Vehicle Engine Maintenance, Fuel Injection System.